Understanding the business of library acquisitions - Schmidt, Karen A. (Chicago : American Library Association, 1999)
The process of obtaining materials for libraries is more complex than ever. The 1990s have witnessed dramatically reduced library budgets while the materials that libraries need have broadened immensely. Library staff must address issues of electronic publishing and licensing, automated communications with vendors, new producers of library materials, and increased possibilities for outsourcing. Stretching limited acquisitions dollars to maintain an appropriate library collection is without doubt a creative and difficult task. This book thoroughly documents the basic principles and practices of acquisitions, including such timeless topics as vendor selection and evaluation, approval plans, acquiring serials, gifts and exchanges, and out-of-print and antiquarian markets.
A very important chapter articulates practical suggestions for successfully managing, organizing, and staffing acquisitions personnel by encouraging managers to lead by example and to 'communicate, communicate, communicate.' There are a number of areas covered in this book that are of utility and significance for even very experienced librarians. First, the chapter that deals with basic accounting theory and business practice as they relate to acquisitions provides vital information. Along related lines, there are two chapters that discuss ethical issues in acquisitions, an important but often neglected area. Additionally, Understanding the Business of Library Acquisitions presents an excellent discussion of outsourcing that includes descriptions of various models that presently exist.
Finally, this volume offers a fine analysis of non-print acquisitions and resources, a subject that emerges as a common thread throughout the book, in addition to a chapter that is devoted to the subject. From the vantage point of health sciences librarians, this topic is critical, because acquiring and managing electronic resources are currently particular areas of concern for them. This compendium has appeared at a time when librarians are very much in need of up-to-date guidelines and information that will help to ensure an efficient and informed acquisitions process.
Acquisitions personnel management, organization, and staffing issues / Lisa German -- Licensing in lieu of acquiring / Trisha L. Davis.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Acquisitions (Libraries) -- United States; Acquisitions (Bibliothèques) -- États-Unis.; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Acquisitions (Libraries); United States; Aanschaf; Bibliotheken; Library & Information Science; Social Sciences; Selecao e aquisicao material (biblioteca)